Pengaruh Ease Of Use Dan E Service Quality Terhadap Keputusan Pengguna Shopee Melalui Trust Pada Generasi Z Sidoarjo - Imamatuz Zakiyah; Farichatul Khafidah; Nuriya Sinta Dewi (Journal of Management and Creative Business, 2025)
The rapid development of digital technology has significantly changed many aspects of life, including the way Generation Z consumes and transacts. With the number of Generation Z members living in Sidoarjo Regency as many as 748,390 people, according to data from the Central Statistics Agency (BPS) in 2020, they are a fairly large demographic for e-commerce trends. This generation is known as an active user of digital technology, especially e-commerce platforms such as Shopee. Shopee as the platform with the most visitors in Indonesia in 2023 recorded 2.35 billion visits, making it an interesting subject to study. This study aims to examine how the quality of electronic services and ease of use influence Shopee user decisions, with trust as a mediating variable. Data were obtained from literature observations and analysis of current e-commerce trends. Previous research findings show mixed results regarding the relationship between these factors, creating opportunities for further exploration. Through a quantitative approach, this study is expected to provide in-depth insight into the consumption behavior of Generation Z in the digital era. The results are not only useful for e-commerce platforms in developing marketing strategies, but can also be an important reference in developing literature related to e-commerce and consumer behavior.